Factors influencing sales performance among SMEs in Malaysia: online platforms adoption as mediating factor - Mohamad Nizam, Muhammad Ameer Syafiq; Kamall Khan, Yasmin; Rochin Demong, Nur Atiqah (Universiti Teknologi Mara Selangor, 2025)
Sales performance is important for businesses to measure the company’s conditions either to grow or sustain in the market. Among the technological landscape, there remain key challenges for businesses to understand the factors that drive sales performance. This study seeks to uncover the retail sector, among small and medium-sized enterprises (SMEs) in Malaysia. This study integrates two theories, TechnologyOrganization-Environment (T-O-E) as the basis of the framework and Attention-Based View (ABV) as a theory supporting it. The framework suggested sales performance as a dependent variable and online platform adoption as a mediator. The key factors in this research will cover perceived compatibility, relative advantages, perceived cost, top management support, and government support that is based on T-O-E framework. Focusing on the retail sector, this conceptual paper provides a deeper understanding of the adoption processes and offers actionable insights to enhance sales performance through technological integration. Adoption of quantitative research methods with a sample size of 384, determined by using the Krejcie and Morgan table with a specific retail industry in Malaysia. The data of this research are based on sources by government agencies specifically through SME Corp Malaysia, Malaysia Corporative and Cooperative Entrepreneur Development (MECD) and Malaysia Digital Economic (MDEC). Furthermore, questionnaires also are distributed among employees and employer among SMEs for collection data. Data will be measured through SmartPLS software (Partial Least Squares Equation Modelling) to determine direct and indirect mediating relationships. These studies provide insight into SMEs in Malaysia and highlight the importance of adopting online platforms into the business and propose a new landscape towards stakeholders in Malaysia.